FARMER’S ADOPTION OF SUSTAINABLE AGRICULTURAL PRACTICES: A REVIEW FROM THE PERSPECTIVE OF RURAL DEVELOPMENT - Nazia Khalida Sulaiman; Siti Hajar Misnan; Mohamad Fadhli Rashid (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Agriculture is an important contributor of rural development. The rural area will benefit economically, socially, and environmentally if the approach of sustainability in agricultural activities is put into practise. This, in turn, will help to make rural development more sustainable in the long run. In a similar light, rural development strategies are also variables that can make it easier for sustainable practises to be implemented in a cost-effective and timely manner. Therefore, this paper aims to examine the significance of dimensions of sustainable rural development as assisting elements in farmer’s decision-making towards adopting Sustainable Agricultural Practices (SAP). Previous empirical studies were analysed for this purpose, and 50 studies conducted in various countries were evaluated in order to discover the main elements impacting the decisions to adopt SAP. The NVivo 12 software was used to code influencing factors gathered from previous studies into dimensions essential to sustainable development of rural area according to the Rural Web model. Findings of this research have found most of the influencing factors that affects farmer’s decision to adopt SAP came from the dimension with institutional elements. Meanwhile, novelty aspect was found to have the least factors recorded in previous studies, which has drawn attention to a gap in previous research. The association between farmers who use innovative methods and their decisions to embrace SAP should be explored further in future studies.